ANALISIS IMPLEMENTASI KEBIJAKAN AKREDITASI SEKOLAH MENENGAH PERTAMA TAHUN 2005-2009 DI PROVINSI DKI JAKARTA - Agus Sulistyanto (Jurnal Manajemen Pendidikan, 2012)
The purpose of this research is to analyze the implementation of accreditation policy of Junior High School period 2005-2009. This research was conducted in the implementation of policies in DKI Jakarta Province with Descriptive and explanations of secondary and primary data methods. The result of research are as follows : (1). The government of DKI Jakarta Province has implemented the accreditation policies are carried out accreditation agency (2). Accreditation agency performance is not optimal due to the change of regulation policy implementation accreditation. (3). There is Junior High School in DKI Jakarta is not feasible in providing educational services, (4). The grade of acreditation inclines to describe the result of quality education, meanwhile the grade of acreditation of international school (RSBI) always describe the result of quality education. It implies that the implementation of accreditation in DKI Jakarta Province, although there are still schools that have not been feasible, but most school accreditation results tend to have a description the actual quality of education.